Data analysis Microsoft with Access 2010 from simple queries to business intelligence - Rockoff, Larry (Course Technology / Cengage Learning, 2012)
DATA ANALYSIS WITH MICROSOFT ACCESS 2010 is an introduction to Access with an emphasis on topics relevant to data analysis. The goal is to help the analyst gain a true understanding of data and the information it contains. Access queries are covered in detail, both in terms of the mechanics of their design, and how they can be used for typical data analysis tasks. The book is written in an easy-to-understand tutorial style, with new topics introduced in a logical and intuitive sequence. Numerous screenshots are included, so you won't need to sit with a computer as you read the book. The author also broadens the concept of data analysis to encompass business intelligence (BI) topics, including valuable material on how to use Access and Excel pivot tables. Additional features include "See the SQL" sidebars that allow interested readers to learn SQL as they are learning Access, and "Focus on Analysis" sidebars that provide details on a number of useful quantitative topics. A companion website has a sample database that correlates with the BI material in the book. In short, this is the only book you'll need to gain a working knowledge of Access, and how it can be used for data analysis